Green credit policy and digital transformation of polluting firms: a quasi-natural experiment from China - Gu, Xuesong; Wang, Yiling (Frontiers in Environmental Science, 2023)
Green credit is an important way to achieve global green development. Using the adoption of the Green Credit Guidance (GCG) policy implemented by the Chinese government in 2012 as a quasinatural experiment, this article examines the impact of the GCG on the digital transformation of highly polluting firms. This research uses text analysis to assess the extent of digital transformation.The empirical findings show that the GCG has a considerable detrimental effect on the digital transformation of significantly polluting businesses. According to the underlying mechanics, the GCG prevents extremely polluting firms from digitalization by tightening financial restrictions and lowering innovation inputs. The GCG's disincentive effect on heavy polluters is especially more pronounced in state-owned listed corporations and the Central and Western areas of China, as demonstrated by heterogeneity research. Our research offers novel ideas for creating a digital economy and promoting sustainable development in emerging developing nations like China.